Produção coletiva de objeto de aprendizagem : o diálogo na universidade e na escola - Rodrigues, Adriana (2006)
In this research, we look for to understand the process of production and socialization to know, proceeding from the development of the learning object Trasnbordando Conhecimento , as well as, its use in the daily one of the lessons of mathematics in average education. For in such a way, we investigate as to know produced them in the daily one of the school they can contribute for the improvement and effectiveness of the dialogue enters the team organizer of learning objects and the professors. Being that, this investigativo work was carried through at two moments, distinct, but that they had been complemented: in the University and the school. The period was understood between June of 2004 to the July of 2005. When answering the two questions that had guided this research, we verify that it had contribution for the formation to know on the systematics of object production of learning and in the object use of learning in the mathematics education; ressignificações of Trasnbordando Conhecimento through the work of projects and also, contribution for the implantation of the educative work with computer science in the schools. We verify that the cycle of constructing, correcting, to reconstruct must continue so that let us have a dynamic education, as well as the rivers its waters goes down follows the course In the tested truth and, thinking metaforicamente, object and people after they are not more the same ones. It had aggregation of knowledge, knowing them individual and collective.